Optimization of brine shrimp lethality test for \(in vivo\) toxicity evaluation of poisonous plant species collected from Quang Tri province: BRINE SHRIMP LETHALITY TEST - Nguyen, Chi Mai; Nguyen, Tuong Van; Pham, Thi Hoe; Vu, Huong Giang; Ninh, Khac Ban; Tran, My Linh (Academia Journal of Biology, 2024)
Plants are natural resources providing several important bioactive compounds for human health. To discover such valuable properties, researchers need to focus on both the pharmacology and toxicity of plant materials. Preliminary toxicity assessment of plants using the Brine Shrimp Lethality Test is a convenient, simple, and effective tool. However, some environmental parameters such as light, temperature and salinity need to be optimized for our own laboratory conditions and Artemia salina cysts produced in Vietnam. The obtained results indicated that the continuous lighting regime, temperature of 30 oC and salinity of 30 ppt are the most suitable parameters for cyst hatching within 24 hours and development of nauplii after 24 hours of hatching. Based on the optimal cyst-hatching procedure, the potential toxicity of 26 extracts from 24 poisonous plant species collected in Quang Tri was determined with median lethal concentration (LC50). The results showed that 3/26 extracts were extremely toxic with LC50 ≤ 10 µg/mL; 10/26 extracts were highly toxic with LC50 from 10 µg/mL to 100 µg/mL; 8/26 extracts were moderately toxic with LC50 from 100 µg/mL to 250 µg/mL; 4/26 extracts had low toxicity with LC50 from 250 µg/mL to 1,000 µg/mL; and 1/26 extract was not toxic with LC50 > 1,000 µg/mL. The presented data could provide scientific evidence for further pharmacological and toxicological investigations of these plant species. The optimal conditions for hatching A. salina cysts in this study will be applied in our laboratory for in vivo toxicity assessment of other plant species.